Towards a redesigned teacher education curriculum in the 21st century: challenges, strategies and implications (2012)
The paper looked at the challenges facing teaching profession in Nigeria currently and identified lapses. Lapses include poor teaching curriculum that is often not easily revised. Despite global changes in the last decade of the last millennium, revolutions in the Information Communication Technology (ICT), one profession has remained the same and that is the teaching profession and specifically provoking is the area of teacher preparation. Though much has been ascribed to the profession, less is done. The profession has become unattractive and cannot attract the best as it used to be. The paper recommended a complete rebranding of the profession and repackaging teacher development programmes.